Windows 10 anniversary update bible - Tidrow, Rob; Boyce, Jim, 1958-; Shapiro, Jeffrey R. (Indianapolis, Indiana : Wiley, 2017)
Your all-inclusive guide to Windows 10 Anniversary Edition Windows 10 Bible, Anniversary Update presents the ultimate reference for enterprise and professional Windows 10 Anniversary Update users. From setup and settings to networking and the daily workflow, this book provides expert guidance on all aspects of the OS. Read from beginning to end for a comprehensive tour of all of the nooks and crannies, or dip in as needed to find quick answers to your most pressing issues formatted as a reference divided into mini-tutorials, this guide delves deep into the Windows 10 Anniversary Update to walk you through every inch of functionality. Personalize your settings, desktop, and security to augment the way you work; configure Windows 10 for enterprise with remote access, groups, and Hyper-V; set up a private network for two or 20 computers, and manage security to keep your content safe everything you need to know is explained here. This book provides clear, authoritative guidance toward every aspect of the old and new to help you take advantage of everything Windows 10 Anniversary Update has to offer. * Customize your Windows 10 Anniversary Update experience * Install and remove hardware and software * Set up your network and configure security * Manage content, connect to printers, and troubleshoot issues Clear your to-do list faster than ever with Cortana voice commands, Windows Ink, Windows Hello, and a cross-platform capability that allows you to integrate a range of platforms including tablets, phones, Raspberry Pi, and even Xbox. Even if you're an experienced user, you're probably missing out on some very cool features let the Windows 10 Bible, Anniversary Update fill the gaps and take your Windows 10 experience to the next level.
Getting started. What's new in Windows 10 ; Navigating the Windows 10 interface ; Getting around the Windows desktop ; Sharing and securing with user accounts ; Troubleshooting startup problems -- Personalizing Windows 10. Protecting yourself with Windows firewall ; Automatic updates as security ; Personalizing the Windows 10 interface ; Personalizing the desktop ; Customizing startup options -- Windows 10 for the enterprise. Setting up Windows 10 Hyper-V ; Configuring Windows 10 Hyper-V ; Using computers remotely ; Managing Windows 10 Hyper-V in an enterprise ; Working in the Cloud and with Azure -- Managing your content. Searching for files and messages on your computer ; Using Cortana for searching ; Metadata and power searches ; Protecting your files -- Printing and managing printers. Installing and managing printers ; Managing print jobs -- Installing and removing programs. Adding and managing Windows 10 applications ; Installing and upgrading Legacy programs ; Getting older programs to run ; Repairing and removing programs ; Setting default programs ; Managing programs and processes ; Troubleshooting software problems -- Hardware and performance tuning. Installing and removing hardware ; Using wireless bluetooth devices ; Performance-tuning your system ; Troubleshooting hardware and performance -- Networking and sharing. Creating a small office or home network ; Sharing resources on a network ; Using shared resources -- Managing Windows 10 in an enterprise. Imaging and deploying Windows 10 ; Using Windows 10 group policies on a network ; Securing Windows 10 for the enterprise -- Appendixes. Appendix A: upgrading to Windows 10 ; Appendix B: Installing Windows 10 on a new system ; Appendix C: universal shortcut keys ; Appendix D: Windows 10 touch gestures.
Includes index.
Keywords: Microsoft Windows (Computer file); Microsoft Windows (Computer file); Operating systems (Computers); COMPUTERS / Operating Systems / Windows Workstation; Operating systems (Computers)